Hodnocení finanční situace podniku a návrhy na její zlepšení - Barnetová, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce je zaměřena na zhodnocení finanční situace podniku Isolit-Bravo, spol. s r.o. za období 2011-2015. První část práce obsahuje teoretické poznatky, které jsou následně využity v praktické části. Ke zhodnocení finanční situace firmy je využíváno vybraných metod finanční analýzy. Poté jsou konkrétní problémy podniku řešeny a na základě vypočtených výsledků jsou uvedeny návrhy. Tyto návrhy by měly dopomoci ke zlepšení finanční situace.

The bachelor thesis is focused on the assessment of the financial situation in the company Isolit-Bravo, spol. s r.o. for period 2011-2015. The first part of the thesis contains theoretical knowledge that is used in the following practical part. To assess the financial situation of the company, some selected methods of financial analysis are used. Then the company’s specific problems are solved and on the basis of achievements some proposalas are presented. It could help to improve the financial situation.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: finanční analýza; rozvaha; výkaz zisku a ztráty; cash-flow; solventnost; rentabilita; financial analysis; balance sheet; profit and loss account; cash-flow; solvency; profitability